To solve this expression, we can use the properties of operations and rules for multiplying and dividing fractions.
First, determine the numerator of the fraction:
(8/9) x (-3/4) = (8 x -3) / (9 x 4) = -24/36
Next, determine the numerator of the second fraction and divide it by the denominator:
(-24/36) ÷ (1/9) = (-24/36) x (9/1) = (-24 x 9) / (36 x 1) = -216/36
Finally, determine the numerator of the third fraction and divide it by the denominator:
(-216/36) ÷ (3/5) = (-216/36) x (5/3) = (-216 x 5) / (36 x 3) = -1080/108
Simplifying the fractional result:
-1080/108 = -10
Therefore, the solution to the expression (8/9) x (-3/4) ÷ (1/9) x (-4/5) ÷ (3/5) is -10.
Use the properties of operations and rules for multiplying and dividing to solve:
(8/9) x (-3/4) divide (1/9) x (-4/5) divide (3/5)
1 answer